2005
DOI: 10.1111/j.0014-3820.2005.tb01768.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspective: Sign Epistasis and Genetic Costraint on Evolutionary Trajectories

Abstract: Epistasis for fitness means that the selective effect of a mutation is conditional on the genetic background in which it appears. Although epistasis is widely observed in nature, our understanding of its consequences for evolution by natural selection remains incomplete. In particular, much attention focuses only on its influence on the instantaneous rate of changes in frequency of selected alleles via epistatic contribution to the additive genetic variance for fitness. Thus, in this framework epistasis only h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
615
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 423 publications
(627 citation statements)
references
References 48 publications
11
615
0
1
Order By: Relevance
“…Of particular interest is the observation of a special type of epistasis termed 'sign epistasis' [2], according to which mutations are beneficial or deleterious depending on the presence or absence of others [3][4][5][6][7][8]. Under sign epistasis, neighbouring mutation combinations display contrasting fitness values, introducing 'ruggedness' in the surface of the fitness landscape.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is the observation of a special type of epistasis termed 'sign epistasis' [2], according to which mutations are beneficial or deleterious depending on the presence or absence of others [3][4][5][6][7][8]. Under sign epistasis, neighbouring mutation combinations display contrasting fitness values, introducing 'ruggedness' in the surface of the fitness landscape.…”
Section: Introductionmentioning
confidence: 99%
“…First, it generates mutational pathways whose intermediate steps are no longer arranged in ascending order. Therefore, the number of pathways accessible by natural selection decreases [2] and successful adaptation becomes contingent upon the identity of first-step mutations [7]. A second, more drastic consequence is the emergence of multiple fitness peaks, which requires a particularly extreme form of epistasis known as reciprocal sign epistasis [9].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, they may limit the number of trajectories towards a fitness optimum that are selectively accessible, with the latter meaning that each mutational step along the trajectory must be fitness increasing . It has been shown that a necessary and sufficient condition for such a reduced accessibility is the presence of so-called sign-epistatic interactions (Weinreich, Watson 2005). Signepistasis refers to the situation where the fitness effect of a mutation A→a can have a different sign depending on the genetic background B or b (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…By definition, not a single path is selectively accessible by single-mutation steps between two peaks (i.e., all paths exhibit fitness decreases). Escape from a suboptimal peak may still be possible, but it involves significantly increased waiting times as specific combinations of genetic changes must appear in a population (Phillips 1996;Weissman et al 2009), or requires large population sizes that support many mutant genotypes at a given time (Weinreich, Watson 2005). Entrapment on sub-optima and its relation to landscape ruggedness has principally been studied theoretically, for instance within the mathematical framework of NK landscape models that were pioneered by Kauffman (Kauffman 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation